Correlation of international prostate symptom score and uroflowmetry in evaluation of benign prostatic hyperplasia - Ugraiah, Anilkumar B.; Shyam, Sharvari (International Surgery Journal, 2020)
Background: Uroflowmetry is a simple non-invasive technique in evaluating patients presenting with Lower urinary tract symptoms (LUTS), to assess voiding patterns, maximum urinary flow (Qmax), average urinary flow (Qave) and voided urine volume. Uroflowmetry is considered mandatory prior to surgical intervention in diagnosis and assessment of men with LUTS. Correlating the International prostrate symptom score (IPSS) with that of uroflowmetry results will allow a better diagnosis and help in determining more appropriate modality of treatment. Therefore, the purpose of our study is to correlate IPSS and the findings of uroflowmetry in evaluation of Benign prostrate hypertrophy (BPH). Methods: This was a prospective study of 50 patients presenting with LUTS diagnosed with BPH. Patient’s symptoms were initially evaluated by administering a pre-treatment IPSS/Quality of Life Score (QoL) and uroflowmetry. All patients underwent Transurethral resection of the prostate (TURP). A post TURP IPSS/QoL score assessment and uroflowmetry was done. Pre-operative IPSS and uroflowmetry results were correlated using spearman’s correlation coefficient. Outcome of IPSS and uroflowmetry following TURP was assessed in terms of percentage improvement. Results: Statistically significant correlation (p<0.05) was seen between IPSS and uroflowmetry results. No correlation was found between prostate volume and IPSS. Significant improvement in symptom severity (IPSS score) and uroflowmetry results was observed in post TURP patients. Conclusion: IPSS is a valuable tool in the evaluation and grading of LUTS. Correlating both IPSS and uroflowmetry results will help in better diagnosis and management of patients. It can also be concluded that IPSS and uroflowmetry can be used for evaluation and monitoring patients following prostate surgery.